AL-KHOREZMI'S CONTRIBUTION TO MATHEMATICS AND MATHEMATICS IN MODERN UZBEKISTAN - Pulatova Kamola Nuralievna (Scholar Express Journals, 2021)
This article reflects the contribution of the great mathematician, astronomer and geographer Muhammad al-Khwarizmi to the science of mathematics and his services as the founder of the science of Algebra. The article also analyzes information on state programs for the development of mathematics in modern Uzbekistan and the ongoing reforms
Keywords: Math; astronomy; geodesy; geometry